EFFECTIVENESS OF SHARINGPLUS MODEL AS ATOOL FOR CONTROLLING STUDENTS’ LEARNING TASKS - Yelfiza, Yelfiza; Siska, Siska; Sesmiyanti, Sesmiyanti; Perpisa, Lili; Zulfariati, Zulfariati (Universitas PGRI Sumatera Barat, 2023)
Controlling undergraduate students’ tasks and supervising the process via online could decrease the quality of the task, since online feedback could not be well transmitted, which then resulted in unexpected revision. Therefore, this research was aimed at finding out the effectiveness of SHARINGPLUS. This research used the action research method, done to twenty students in even semester 2020/2021. The model contained kinds of tasks with indicators and sub-indicators, list of students, and task options related to their final grades. The model contains eleven stages for every kind of task, but the students who succeed in doing the task until stage 4 do not need to do the following steps. Only the students with difficulty should follow the steps until the end. Findings showed that 45 % participants could follow 4 processes (SHAR). They worked in R stage repeatedly, since there was no limitation of task submission. The remaining students found difficulty in working in the system so that they could not finish their tasks in the system. Thus, conclusion can be stated that the model was not yet effective to make students work as expected so that it needs more development.